2006
DOI: 10.1242/jcs.02852
|View full text |Cite
|
Sign up to set email alerts
|

A role for the ELAV RNA-binding proteins in neural stem cells: stabilization ofMsi1mRNA

Abstract: Post-transcriptional regulation exerted by neural-specific RNA-binding proteins plays a pivotal role in the development and maintenance of the nervous system. Neural ELAV proteins are key inducers of neuronal differentiation through the stabilization and/or translational enhancement of target transcripts bearing the AU-rich elements (AREs), whereas Musashi-1 maintains the stem cell proliferation state by acting as a translational repressor. Since the gene encoding Musashi-1 (Msi1) contains a conserved ARE in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 77 publications
2
79
0
Order By: Relevance
“…Presenslin-1 deletion results in premature neuronal differentiation and suppression of miR-9 expression (Krichevsky et al, 2003), further supporting the involvement of the Notch pathway in ethanol's actions. In contrast to Jag-1, the brain-specific RNA binding protein ELAVL2, a presumptive target of miR-335, -153, and -9, promotes neuronal maturation by binding to the 3Ј untranslated regions of mRNAs to suppress non-neuronal fates and promote neuronal identity (Akamatsu et al, 1999(Akamatsu et al, , 2005Yano et al, 2005;Ratti et al, 2006). Previous evidence indicates that ELAVL2 also promotes neuron-specific alternate splicing and alternate polyadenylation (Zhu et al, 2007) to expand the transcriptome repertoire of neuron specific genes.…”
Section: Mechanisms Mediating Ethanol Sensitivity Of Mirnasmentioning
confidence: 99%
“…Presenslin-1 deletion results in premature neuronal differentiation and suppression of miR-9 expression (Krichevsky et al, 2003), further supporting the involvement of the Notch pathway in ethanol's actions. In contrast to Jag-1, the brain-specific RNA binding protein ELAVL2, a presumptive target of miR-335, -153, and -9, promotes neuronal maturation by binding to the 3Ј untranslated regions of mRNAs to suppress non-neuronal fates and promote neuronal identity (Akamatsu et al, 1999(Akamatsu et al, , 2005Yano et al, 2005;Ratti et al, 2006). Previous evidence indicates that ELAVL2 also promotes neuron-specific alternate splicing and alternate polyadenylation (Zhu et al, 2007) to expand the transcriptome repertoire of neuron specific genes.…”
Section: Mechanisms Mediating Ethanol Sensitivity Of Mirnasmentioning
confidence: 99%
“…It can be regulated by ELAV or HuR by maintaining the stabilization of its mRNA or accumulation of mRNA translation (7,8), as well as by tumor suppressor microRNAs (9). It was first found in Drosophila as a determinant of sensory organ development (10) and highly conserved across species (11) with essential roles in the stem cell maintenance, nervous system development and tumorigenesis (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Ratti et al (2006) reported post-transcriptional regulation of Msi1 mRNA by embryonic lethal abnormal vision (ELAV), an RNA-binding protein of Drosophila (Ratti et al, 2006). This is an interesting result because it may imply that some kind of cascade of post-transcriptional regulation contributes to neurogenesis, in addition to other machinery, i.e., signal transduction, transcriptional regulation, and post-translational modification.…”
Section: Novel Finding For the Functions Of Musashi Proteinsmentioning
confidence: 99%